Race in the hood : conflict and violence among urban youth - Pinderhughes, Howard (University of Minnesota Press, 1997)
A compelling study of the origins of racial conflict and violence in America. "We'll just be hanging out, partying. And somebody will say, 'Hey, let's go on a mission.' That's when you go looking for people who don't belong in the neighborhood, and you beat 'em up. Sometimes we go out lookin' for blacks to jump. Sometimes we look for anybody who ain't supposed to be there." Sal, Avenue T BoysWhy are racial conflict and violence among the most enduring problems in American society? Why do some youths express racism violently while others develop tolerance and respect for those who are different.
Keywords: Juvenile delinquency -- New York (State) -- New York -- Case studies.; Youth -- Crimes against -- New York (State) -- New York -- Case studies.; Hate crimes -- New York (State) -- New York -- Case studies.; New York (N.Y.) -- Race relations -- Case studies.; Youth -- New York (State) -- New York -- Attitutes.; Délinquance juvénile -- New York (État) -- New York -- Études de cas.; Crimes haineux -- New York (État) -- New York -- Études de cas.; SOCIAL SCIENCE -- Anthropology -- Cultural.; Hate crimes.; Juvenile delinquency.; Race relations.; Youth -- Crimes against.; New York (State) -- New York.; Case studies.